Internalization of Religious Character Education in the Organization of Persaudaraan Setia Hati Terate (PSHT) - Maftukhurrohman Fawaz; Ahmad Shofiyuddin Ichsan; Anwar Masduki Azzam (Journal of Contemporary Islamic Education, 2025)
The many adverse incidents that had befallen the Persaudaraan Setia Hati Terate (PSHT) organization in Indonesia had caused concern for the wider community. Therefore, there needed to be an understanding that this organization did not teach such negative things. So, in this research, the researchers wanted to show how the internalization of religious (Islamic) character education in the PSHT organization at Sanggar Kasatriyan Pundong Bantul Yogyakarta. The researchers used qualitative research with the type of field research. The data collection techniques used by the researcher were observation, interviews, and documentation. Meanwhile, the researchers used data analysis techniques to reduce data, review data, and draw conclusions. The research results showed that PSHT Sanggar Kasatriyan Pundong carried out various internalizations of religious education through habituations and learning good things, feeling and loving what had been learned, and implementing religious activities. The results of the internalization of religious education were that students were trained to be role models, realized every mistake they made, reduced naughtiness, and continued learning to be religiously obedient.